Stress corrosion cracking of a copper elbow fitting. (August 2018) - Metcalfe, R.G.; Pearce-Boltec, N.
Abstract: This paper presents the results of an examination of cracking in a phosphorous deoxidised copper fitting that had been installed in a liquid nitrogen line. The service life of the fitting was reported to be three to four years. Failure was a result of the Stress Corrosion Cracking (SCC) from the outside surface that had been placed in tension by the pipeline being chocked with a block of wood to locally raise the line above a cable tray. The active species for SCC was suspected of being Amines in the Polyurethane insulation. Highlights: The room temperature Intergranular SCC of a high purity copper fitting is described. The active species is proposed to be amines associated with the polyurethane foam insulation. Stresses present associated with installation